Determinants of School Dropout Rates Across the Districts of Telangana and Andhra Pradesh States An Econometric Study - Muravath, Rajanna; Sadanandam, A. (JOURNAL OF INDIAN EDUCATION, 2018)
Despite sizeable spending by the State on education at school level, millions of students in the age group of 6 to 13 are found out of school because of high dropout rates. Many studies found different factors responsible for this, such as literacy and poverty levels of parents, availability of adequate infrastructure facilities in schools, pupil-teacher ratio, trained teachers, distance and accessibility of school, etc. This study attempts to identify the important factors which determine the school dropout rate by using linear multiple regression method on cross section data of Telangana and Andhra Pradesh (the combined Andhra Pradesh) for the year 2013–14. For the purpose of formulation of appropriate policy, the determinants are identified in an order of their degree of influence. Prevailing literacy levels, percentage of rural population and pupilteacher ratio in the district are found to be significant factors.